One-pot synthesis and characterization of a BSA-Cu2S/CuS quantum dots drug delivery system based on biuret’s reaction - Porfirio Estrada-Rojas; Juan Francisco Hernández-Paz; Claudia Alejandra Rodríguez-González; Mónica Elvira Mendoza-Duarte; Santos Adriana Martel-Estrada; Laura Elizabeth Valencia-Gómez; Héctor Camacho-Montes; Imelda Olivas-Armendáriz (Materials Research Express)
Research on chalcogenide-based quantum dots (QDs) has advanced significantly over recent decades, largely due to their excellent optical properties, particularly photoluminescence, and relatively low toxicity. Among these, Cu _2 S and CuS quantum dots have demonstrated notable photothermal effects and antibacterial activity, making them promising candidates for various biomedical applications, including cancer treatment. This study focuses on the synthesis of CuS and Cu _2 S quantum dots functionalized with bovine serum albumin (BSA), marking an important step toward their potential biomedical use. The functionalization was achieved through a one-pot synthesis method, characterized by its ability to offer higher chemical yield, elimination of toxic solvents, and provide a method that is simple, economical, and well-controlled. This synthesis produced four samples with varying BSA concentrations. Due to the lower protein concentration, which provides fewer nucleation sites, sample A (BSA concentration 5 mg ml ^−1 ) showed a particle size distribution over 100 nm and low stability over time. Sample B (25 mg ml ^−1 BSA) and C (50 mg ml ^−1 BSA) showed excellent stability and particle sizes within the expected range for Cu _2 S and CuS quantum dots (<2.4 nm). Sample D was synthesized with lower BSA concentration (2.5 mg ml ^−1 ) and was used only for comparison in few analyses. Fourier-transform infrared (FTIR) spectroscopy confirmed the structural integrity of BSA after functionalization, while x-ray diffraction (XRD) analysis verified the formation of CuS and Cu _2 S crystals. Additional tests, including fluorescence and UV–vis spectroscopy, validated the optical properties of the quantum dots. Transmission electron microscopy (TEM) confirmed crystalline structure of the CuS and Cu _2 S quantum dots, with particle size measurements aligning with expectations. Finally, MTT assays confirmed that the synthesized quantum dots are non-toxic, further supporting their potential for biomedical applications.